Non-Conviction Based Asset Forfeiture Policy Concept Through In Rem Lawsuit Based on Economic Analysis of Law - Sakinah, Tri Indah; Sumardiana, Benny (Fakultas Hukum Universitas Islam Jakarta, 2025)
The mismatch between state losses and the amount of assets recovered in handling corruption cases is caused by inefficient regulations. Indonesian legal system has yet to firmly regulate asset forfeiture mechanisms without criminal conviction through in rem lawsuits. This study aims to examine the Non-Conviction Based (NCB) asset forfeiture policy concept through in rem lawsuit based on Economic Analysis of Law (EAL) approach in Indonesia. This research uses a normative juridical method, focusing on the analysis of asset forfeiture regulations in Indonesia within several other countries, and also explores the relationship between asset forfeiture policies and EAL approach. The findings show that NCB Asset Forfeiture through in rem lawsuits is a crucial step to enhance the effectiveness of anti-corruption law enforcement in Indonesia. The development of this policy aligns with the provisions of UNCAC, which provide a legal basis for countries to conduct asset forfeiture without waiting for a final and binding court verdict. By integrating the EAL approach, this policy can ensure economic efficiency in the recovery of state losses while eliminating economic incentives for corrupt actors. In conclusion, the enactment of the Asset Forfeiture Bill is urgent to establish a more effective, solution-oriented, and adaptive legal enforcement system against corruption as an economic crime.